Molecular sieve activation powder for extending adhesive curing time and preparation method thereof
Through the use of molecular screening powder and modified additives in the adhesive, the problem of moisture and volatile substances in the adhesive in the adhesive, and the stability and solidification effect of the adhesive.
Patent Information
- Application Number
- CN202411426069.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The presence of moisture and volatile substances in existing adhesives leads to bubbles, cracks, decreased strength and shortened service life. The traditional solutions are inefficient and may introduce new problems.
Molecular sieve activated powder is used to improve its moisture and gas adsorption performance through the preparation method of matrix sieve powder, including specific raw material ratio and process order, and add modified additives to enhance adsorption performance and stability.
Significantly inhibit the foaming phenomenon of polyurethane colloids, extend the curing time of the adhesive, provide more open time, and improve the adhesive adhesive strength and surface smoothness.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of adhesive additives, and in particular to a molecular sieve activation powder for prolonging the curing time of an adhesive and a preparation method thereof. Background Art
[0002] In the process of adhesive preparation and application, there is a long-standing technical challenge, that is, how to effectively control and reduce the moisture and other volatile substances in the system, which not only affect the initial mixing performance of the adhesive, but also may cause bubbles, cracks, strength loss and shortened service life of the final product. Traditional solutions, such as physical stirring, heating and volatilization, are often inefficient and may introduce new problems, such as high energy consumption, long processing time and potential damage to product performance.
[0003] As an innovative technology, molecular sieve activation powder was developed to address the above-mentioned problems. Based on its unique microporous structure and highly selective adsorption performance, this type of material can efficiently adsorb and remove moisture and harmful gases (such as CO2, H2S, etc.) in the system at the molecular level, thereby significantly improving the purity and stability of the adhesive. Especially in polymer adhesive systems such as polyurethane, epoxy resin, and acrylate, the application of molecular sieve activation powder can effectively inhibit the generation of bubbles caused by moisture, ensuring the smooth progress of the curing process and the surface smoothness and bonding strength of the cured product.
[0004] Although molecular sieve activation powder has good adsorption properties, in practical applications, how to balance the selective adsorption of different molecules (especially water and solvents, low molecular weight reaction by-products) and the total adsorption capacity is still a technical problem. In addition, when existing adhesive products are used with molecular sieves, the open time of the adhesive will be shortened, which is not conducive to the application of the adhesive. This is actually related to the acidity and alkalinity of the adhesive system and the molecular sieve system itself. Further tests have found that the stronger the alkalinity in the adhesive system, the shorter the open time when using molecular sieve activation powder. In addition, the main component of general zeolite molecular sieve activation powder is alkali metal or alkaline earth metal aluminosilicate, and the strong alkalinity further exacerbates this phenomenon.
[0005] Therefore, in order to effectively solve the above-mentioned problems, the present application provides a molecular sieve activation powder for extending the curing time of an adhesive and a preparation method thereof. The molecular sieve activation powder prepared in the present application can retain a good adhesive curing extension effect while ensuring excellent moisture and gas adsorption properties, thereby providing more open time for the use of the adhesive, and in particular can effectively delay the curing speed of the polyurethane adhesive, that is, extend the curing time required for the polyurethane adhesive, thereby making the adhesive operable for a longer time and facilitating the application of the adhesive, and has very excellent market and application value. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present application provides a molecular sieve activation powder for prolonging the curing time of the adhesive, the raw materials including: 60-90 parts of base sieve powder, 10-25 parts of modified additives, 5-20 parts of organic acid anhydride, and 5-10 parts of polysiloxane.
[0007] As a preferred solution, the mass ratio of the base sieved powder to the modified additive is (7~8.5):(1.2~2).
[0008] As a preferred solution, the mass ratio of the base sieved powder to the modified additive is (7.5~8):(1.5~2).
[0009] As a preferred solution, the mass ratio of the base sieved powder to the modified additive is 8:1.8.
[0010] As a preferred solution, the preparation method of the matrix sieve powder includes the following steps: S1: mixing an aluminum source and a sodium source, adding them to deionized water, and stirring them evenly; S2: heating the solution to 40-60°C, adding a silicon source to the S1 solution, stirring for 20-30 minutes to mix evenly, and adjusting the water content during the stirring until a gel product is formed after the stirring is completed; S3: placing the gel product in a crystallization kettle, heating the solution to 90-100°C at a speed of 2-4°C / min, and stirring the solution at a speed of 100-200 rpm for 3-5 hours to crystallize the gel product; S4: after the crystallization is completed, naturally reducing the temperature. The mixture is stably stored at room temperature for 30 to 50 hours for aging, and after aging, it is filtered to obtain filter cake I; S5: filter cake I is added to an ion exchange kettle, and appropriate amount of deionized water is added to disperse and stir for 20 to 30 minutes until it is uniform, and after sufficient water washing, it is filtered twice to obtain filter cake ⅠⅠ; S6: filter cake ⅠⅠ is added to an ion exchange kettle, and appropriate amount of deionized water and ion exchange agent are added. The mixture is dispersed and stirred for 20 to 30 minutes until it is uniform, and then filtered three times to obtain filter cake ⅠⅠⅠ; S7: filter cake ⅠⅠⅠ is ground into powder and calcined at 500 to 600℃ for complete activation, and then the material is discharged.
[0011] As a preferred solution, the aluminum source is at least one of aluminum oxide, aluminum hydroxide, sodium aluminate, and aluminum chloride.
[0012] As a preferred solution, the aluminum source is sodium aluminate.
[0013] As a preferred solution, the sodium source is at least one of sodium silicate, sodium hydroxide and sodium chloride.
[0014] As a preferred solution, the sodium source is sodium hydroxide.
[0015] As a preferred solution, the silicon source is sodium silicate or potassium silicate.
[0016] As a preferred solution, the silicon source is sodium silicate.
[0017] As a preferred solution, the ion exchanger is at least one of potassium chloride, calcium chloride, ammonium chloride, magnesium chloride and zinc chloride.
[0018] As a preferred solution, the ion exchanger is potassium chloride.
[0019] As a preferred solution, the mass ratio of the aluminum source, sodium source and silicon source is (1~1.2):(0.8~1.2):(2~2.5).
[0020] As a preferred solution, the mass ratio of the aluminum source, the sodium source and the silicon source is (1~1.1):(1~1.2):(2.2~2.4).
[0021] As a preferred solution, the mass ratio of the aluminum source, the sodium source and the silicon source is 1:1.1:2.2.
[0022] As a preferred solution, the mass ratio of deionized water to filter cake I in S5 is (1-1.2): (0.4-0.6).
[0023] As a preferred solution, the mass ratio of deionized water to filter cake I in S5 is 1:0.5.
[0024] As a preferred solution, the mass ratio of deionized water, filter cake Ⅱ and ion exchanger in S6 is (1-1.2): (0.4-0.6): (0.1-0.2).
[0025] As a preferred solution, the mass ratio of deionized water, filter cake II and ion exchanger in S6 is 1:0.5:0.1.
[0026] In the present application, the preparation of the above-mentioned matrix sieve powder can effectively improve the moisture and gas adsorption performance of the molecular sieve activation powder, can significantly inhibit the foaming phenomenon of the polyurethane colloid, and has a good adhesive curing extension effect, providing more open time for the use of the adhesive. In the present application, by selecting the raw material ratio and process sequence of the matrix sieve powder, not only the porosity and pore depth of the matrix sieve powder are effectively increased, but also the lattice defects after crystallization are reduced through the control of the crystallization process, the activity of the surface group is reduced, and the purity of the crystallization is greatly improved, thereby avoiding the influence of the alkaline substances in the solvent on the final matrix sieve powder performance, and greatly reducing the alkalinity of the matrix sieve powder during the application process, thereby avoiding the influence of the molecular sieve activation powder's own alkalinity bias on the overall curing time and open time of the adhesive.
[0027] As a preferred scheme, the preparation method of the modified additive includes the following steps: S1: adding chromium nitrate, terephthalic acid and acetic acid to deionized water and stirring evenly at room temperature, then adding to a closed reactor, gradually heating to 200-210°C at a heating rate of 2°C / min, controlling the reactor pressure to be 1.8-2.2MPa, then continuously stirring to react for 8-12h, and after the reaction is completed, cooling to room temperature and washing, filtering and drying to obtain a particle product; S2: adding the particle product and the composite particles to a mixed solution of water and ethanol, adding ammonia water and tetraethyl orthosilicate, heating to 60-65°C, reacting for 2-4h, and filtering, washing and drying the product after completion.
[0028] As a preferred solution, the mass ratio of chromium nitrate, terephthalic acid and acetic acid is (2.5-3.5): (0.8-1.4): (10-14).
[0029] As a preferred solution, the mass ratio of chromium nitrate, terephthalic acid and acetic acid is (2.5-3): (0.8-1): (10-12).
[0030] As a preferred solution, the composite particles are zinc oxide or titanium dioxide.
[0031] As a preferred solution, the composite particles are zinc oxide.
[0032] As a preferred solution, the average particle size of the composite particles is 10-30 nm.
[0033] As a preferred solution, the mass ratio of the particle product, the composite particles and tetraethyl orthosilicate is (1.5-2): (0.3-0.5): (0.4-0.5).
[0034] The second aspect of the present application provides a method for preparing the above-mentioned molecular sieve activation powder for extending the curing time of the adhesive, and the preparation method comprises the following steps: S1: adding the base sieve powder to a mixed solution of water and ethanol and dispersing it evenly; S2: adding a mixed ethanol solution of a modified additive and polysiloxane, and then dripping an aqueous solution containing an organic acid anhydride into the reaction solution, heating it to 55~65℃ and stirring it for 2~3h, and after completion, ultrasonically dispersing the product at 40~50℃ and 200~250W power for 0.5~1h, and after completion, filtering and drying the product, and obtaining the product.
[0035] As a preferred solution, the average particle size of the modified additive is 500-650 nm.
[0036] As a preferred solution, the mass ratio of the modified additive, polysiloxane and organic anhydride is (1.2~2): (0.2~0.4): (0.8~1.2).
[0037] As a preferred solution, the mass ratio of the modified additive, polysiloxane and organic anhydride is (1.5-2): (0.25-0.3): (1-1.2).
[0038] As a preferred solution, the polysiloxane is 3-aminopropyltriethoxysilane.
[0039] As a preferred solution, the organic acid anhydride is succinic anhydride or glutaric anhydride.
[0040] In this application, by adding modified additives, not only the adsorption performance of the molecular sieve active powder is further improved, but also the stability of the molecular sieve composite particles can be greatly enhanced, the dispersion effect of the system can be improved, and the surface viscosity can be reduced, thereby improving the performance of the adhesive in all aspects. The modified particle skeleton structure can be coordinated and combined with the surface active groups of the matrix sieve powder, and the sol silicon formed is protectively bonded and fixed. The formed composite structure not only increases the total specific surface area and porosity of the unit number of particles, but the micropores of the skeleton particles can also assist in the absorption of water molecules, and always maintain the fixed preservation of water at a limited temperature. At the same time, the coordinated zinc oxide / titanium dioxide particles can use an appropriate number of surface active groups to guide the water molecules in the adhesive system, so that the molecular sieve active powder can capture water molecules in a short time, and quickly adsorb through the path, while increasing the total amount of adsorption, greatly improving the adsorption speed.
[0041] The beneficial effects of this application are:
[0042] 1. The molecular sieve activation powder for extending the curing time of an adhesive provided in the present application can retain a good adhesive curing extension effect while ensuring excellent moisture and gas adsorption performance, thereby providing more open time for the use of the adhesive, and in particular, can effectively delay the curing speed of the polyurethane adhesive, that is, extend the curing time required for the polyurethane adhesive, so that the adhesive can be operated for a longer time, which is convenient for the application of the adhesive, and has very excellent market and application value.
[0043] 2. The molecular sieve activation powder for extending the curing time of the adhesive provided in the present application can effectively improve the moisture and gas adsorption performance of the molecular sieve activation powder through the preparation of the base sieve powder, can significantly inhibit the foaming phenomenon of the polyurethane colloid, and has a good adhesive curing extension effect, providing more open time for the use of the adhesive.
[0044] 3. The molecular sieve activation powder for extending the curing time of the adhesive provided in the present application has a raw material ratio of the base sieve powder and a selection of the process sequence, which not only effectively increases the porosity and pore depth of the base sieve powder, but also reduces the lattice defects after crystallization, reduces the activity of the surface groups, and greatly improves the purity of the crystals through the control of the crystallization process, thereby avoiding the influence of alkaline substances in the solvent on the final performance of the base sieve powder, and greatly reduces the alkalinity of the base sieve powder during the application process, thereby avoiding the influence of the molecular sieve activation powder's own alkaline bias on the overall curing time and open time of the adhesive.
[0045] 4. The molecular sieve activation powder provided in this application for extending the curing time of the adhesive, with the addition of modified additives, not only further improves the adsorption performance of the molecular sieve activation powder, but also can greatly enhance the stability of its molecular sieve composite particles, improve its system dispersion effect, reduce surface viscosity, and thus improve the adhesive performance in all aspects. The modified particle skeleton structure can be coordinated and bound by the surface active groups of the matrix sieve powder, and the protective bonding and fixing is performed by the formed sol silica. The formed composite structure not only increases the total specific surface area and porosity of the unit number of particles, but the micropores of the skeleton particles can also assist in the absorption of water molecules, and always keep the fixed preservation of water at a limited temperature. At the same time, the coordinated zinc oxide / titanium dioxide particles can use an appropriate number of surface active groups to guide the path of water molecules in the adhesive system, so that the molecular sieve activation powder can capture water molecules in a short time. DETAILED DESCRIPTION
[0046] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0047] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0048] Example 1
[0049] Embodiment 1 The first aspect provides a molecular sieve activation powder for prolonging the curing time of an adhesive, the raw materials comprising: 80 parts of base sieve powder, 18 parts of modified additives, 11 parts of organic acid anhydride, and 0.28 parts of polysiloxane.
[0050] The polysiloxane is 3-aminopropyltriethoxysilane; and the organic acid anhydride is succinic anhydride.
[0051] The preparation method of the matrix sieve powder comprises the following steps, calculated by mass: S1: 1 part of aluminum source and 1.1 parts of sodium source are mixed and added to 30 parts of deionized water, and stirred evenly; S2: the temperature is raised to 55°C, 2.2 parts of silicon source are added to the S1 solution, and the mixture is stirred for 25 minutes to be evenly mixed, during which the water content is adjusted until a gel product is formed after the stirring is completed; S3: the gel product is placed in a crystallization kettle, the temperature is raised to 100°C at 3.5°C / min, and the rotation speed is stirred at 150rpm for 4 hours to crystallize the gel product; S4: after the crystallization is completed, the temperature is naturally reduced to 50°C. Stably store at room temperature for 48 hours for aging, and filter press after aging to obtain filter cake I; S5: add 5 parts of filter cake I to an ion exchange kettle, add 10 parts of deionized water and disperse and stir for 25 minutes until uniform, wash thoroughly with water and filter press twice to obtain filter cake ⅠⅠ; S6: add 5 parts of filter cake ⅠⅠ to an ion exchange kettle, add 10 parts of deionized water and 1 part of ion exchanger, mix and disperse and stir for 30 minutes until uniform, and filter press three times to obtain filter cake ⅠⅠⅠ; S7: grind filter cake ⅠⅠⅠ into powder and calcine at 550℃ to activate it completely, and then discharge it.
[0052] The aluminum source is sodium aluminate; the sodium source is sodium hydroxide; the silicon source is sodium silicate; and the ion exchanger is potassium chloride.
[0053] The preparation method of the modified additive includes the following steps: S1: adding 2.8 parts of chromium nitrate, 0.96 parts of terephthalic acid and 11.5 parts of acetic acid to 250 parts of deionized water, stirring evenly at room temperature of 30°C, then adding to a closed reactor, gradually heating to 210°C at a heating rate of 2°C / min, controlling the pressure of the reactor to be 2.1MPa, and then continuously stirring to react for 10 hours. After the reaction is completed, cooling to room temperature and washing, filtering and drying to obtain a particle product; S2: adding 1.8 parts of the particle product and 0.42 parts of the composite particles to a mixed solution of 100 parts of water and ethanol (water: ethanol = 4:1), adding 0.12 parts of ammonia water and 0.5 parts of tetraethyl orthosilicate, heating to 60°C, reacting for 2.5 hours, and filtering, washing and drying the product after completion to obtain.
[0054] The composite particles are zinc oxide, and the average particle size of the zinc oxide is 15 nm.
[0055] The average particle size of the modified additive is 584 nm.
[0056] The second aspect of the present embodiment provides a method for preparing the above-mentioned molecular sieve activation powder for extending the curing time of the adhesive, and the preparation method comprises the following steps, measured in parts by mass: S1: adding 80 parts of base sieve powder to a mixed solution of 1000 parts of water and ethanol (water: ethanol = 4:1) and dispersing them evenly; S2: adding a mixed ethanol solution of 18 parts of modified additives and 0.28 parts of polysiloxane (a total of 120 parts), and then dripping an aqueous solution containing 11 parts of organic acid anhydride (a total of 100 parts) into the reaction solution, heating to 60°C and stirring for 3 hours, and after completion, ultrasonically dispersing the product at 50°C and 220W power for 1 hour, and filtering and drying the product after completion, and obtaining the product.
[0057] Example 2
[0058] Example 2 The first aspect provides a molecular sieve activation powder for extending the curing time of an adhesive, the raw materials comprising: 75 parts of base sieve powder, 12 parts of modified additives, 9 parts of organic acid anhydride, and 0.2 parts of polysiloxane.
[0059] The polysiloxane is 3-aminopropyltriethoxysilane; and the organic acid anhydride is succinic anhydride.
[0060] The preparation method of the matrix sieve powder comprises the following steps, calculated by mass: S1: 1 part of aluminum source and 1.1 parts of sodium source are mixed and added to 30 parts of deionized water, and stirred evenly; S2: the temperature is raised to 55°C, 2.2 parts of silicon source are added to the S1 solution, and the mixture is stirred for 25 minutes to be evenly mixed, during which the water content is adjusted until a gel product is formed after the stirring is completed; S3: the gel product is placed in a crystallization kettle, the temperature is raised to 100°C at 3.5°C / min, and the rotation speed is stirred at 150rpm for 4 hours to crystallize the gel product; S4: after the crystallization is completed, the temperature is naturally reduced to 50°C. Stably store at room temperature for 48 hours for aging, and filter press after aging to obtain filter cake I; S5: add 5 parts of filter cake I to an ion exchange kettle, add 10 parts of deionized water and disperse and stir for 25 minutes until uniform, wash thoroughly with water and filter press twice to obtain filter cake ⅠⅠ; S6: add 5 parts of filter cake ⅠⅠ to an ion exchange kettle, add 10 parts of deionized water and 1 part of ion exchanger, mix and disperse and stir for 30 minutes until uniform, and filter press three times to obtain filter cake ⅠⅠⅠ; S7: grind filter cake ⅠⅠⅠ into powder and calcine at 550℃ to activate it completely, and then discharge it.
[0061] The aluminum source is sodium aluminate; the sodium source is sodium hydroxide; the silicon source is sodium silicate; and the ion exchanger is potassium chloride.
[0062] The preparation method of the modified additive includes the following steps: S1: adding 2.8 parts of chromium nitrate, 0.96 parts of terephthalic acid and 11.5 parts of acetic acid to 250 parts of deionized water, stirring evenly at room temperature of 30°C, then adding to a closed reactor, gradually heating to 210°C at a heating rate of 2°C / min, controlling the pressure of the reactor to be 2.1MPa, and then continuously stirring to react for 10 hours. After the reaction is completed, cooling to room temperature and washing, filtering and drying to obtain a particle product; S2: adding 1.8 parts of the particle product and 0.42 parts of the composite particles to a mixed solution of 100 parts of water and ethanol (water: ethanol = 4:1), adding 0.12 parts of ammonia water and 0.5 parts of tetraethyl orthosilicate, heating to 60°C, reacting for 2.5 hours, and filtering, washing and drying the product after completion to obtain.
[0063] The composite particles are zinc oxide, and the average particle size of the zinc oxide is 15 nm.
[0064] The average particle size of the modified additive is 584 nm.
[0065] The second aspect of the present embodiment provides a method for preparing the above-mentioned molecular sieve activation powder for extending the curing time of the adhesive, and the preparation method comprises the following steps, measured in parts by mass: S1: adding 80 parts of base sieve powder to a mixed solution of 1000 parts of water and ethanol (water: ethanol = 4:1) and dispersing them evenly; S2: adding a mixed ethanol solution of 18 parts of modified additives and 0.28 parts of polysiloxane (a total of 120 parts), and then dripping an aqueous solution containing 11 parts of organic acid anhydride (a total of 100 parts) into the reaction solution, heating to 60°C and stirring for 3 hours, and after completion, ultrasonically dispersing the product at 50°C and 220W power for 1 hour, and filtering and drying the product after completion, and obtaining the product.
[0066] Comparative Example 1
[0067] The specific implementation of this comparative example is basically the same as that of Example 1, except that the raw materials of the molecular sieve activation powder for extending the curing time of the adhesive include: 120 parts of base sieve powder, 10 parts of modified additives, 11 parts of organic acid anhydride, and 0.28 parts of polysiloxane.
[0068] Comparative Example 2
[0069] The specific implementation of this comparative example is basically the same as that of Example 1, except that the molecular sieve activation powder for extending the curing time of the adhesive comprises: 80 parts of base sieve powder, 18 parts of modified additives, 4.2 parts of organic acid anhydride, and 0.11 parts of polysiloxane.
[0070] Comparative Example 3
[0071] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the matrix sieve powder includes the following steps, calculated by mass: S1: 1 part of aluminum source and 1.1 parts of sodium source are mixed and added to 30 parts of deionized water, and stirred evenly; S2: the temperature is raised to 55°C, 2.2 parts of silicon source are added to the S1 solution, and the mixture is stirred for 25 minutes to mix evenly, during which the water content is adjusted until a gel product is formed after the stirring is completed; S3: the gel product is placed in a crystallization kettle, the temperature is raised to 100°C at 3.5°C / min, and the mixture is stirred at 150 rpm for 4 hours to allow the gel product to crystallize. ; S4: After the crystallization is completed, it is naturally cooled to room temperature and stably stored for 48 hours for aging. After the aging is completed, it is filtered to obtain filter cake I; S5: 5 parts of filter cake I are added to the ion exchange kettle, and 5 parts of deionized water are added to disperse and stir for 25 minutes until it is uniform, and then washed with water and filtered twice to obtain filter cake ⅠⅠ; S6: 5 parts of filter cake ⅠⅠ are added to the ion exchange kettle, 25 parts of deionized water and 0.25 parts of ion exchanger are added, mixed and dispersed and stirred for 30 minutes until it is uniform, and then filtered three times to obtain filter cake ⅠⅠⅠ; S7: Grind filter cake ⅠⅠⅠ into powder and roast at 550℃ for complete activation, and then discharge the material.
[0072] Comparative Example 4
[0073] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the matrix sieve powder includes the following steps, calculated by mass: S1: 3 parts of aluminum source and 1.8 parts of sodium source are mixed and added to 30 parts of deionized water, and stirred evenly; S2: the temperature is raised to 55°C, 0.6 parts of silicon source are added to the S1 solution, and the mixture is stirred for 25 minutes to mix evenly, during which the water content is adjusted until a gel product is formed after the stirring is completed; S3: the gel product is placed in a crystallization kettle, the temperature is raised to 100°C at 3.5°C / min, and the mixture is stirred at 150 rpm for 4 hours to allow the gel product to crystallize. ; S4: After the crystallization is completed, it is naturally cooled to room temperature and stably stored for 48 hours for aging. After the aging is completed, it is filtered to obtain filter cake I; S5: 5 parts of filter cake I are added to the ion exchange kettle, 10 parts of deionized water are added, and dispersed and stirred for 25 minutes until uniform, and then filtered twice after sufficient water washing to obtain filter cake ⅠⅠ; S6: 5 parts of filter cake ⅠⅠ are added to the ion exchange kettle, 10 parts of deionized water and 1 part of ion exchanger are added, the mixture is dispersed and stirred for 30 minutes until uniform, and then filtered three times to obtain filter cake ⅠⅠⅠ; S7: The filter cake ⅠⅠⅠ is ground into powder and calcined at 550℃ for complete activation, and then the material is discharged.
[0074] Comparative Example 5
[0075] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified additive comprises the following steps: S1: adding 4.5 parts of chromium nitrate, 1.85 parts of terephthalic acid and 3.5 parts of acetic acid to 250 parts of deionized water, stirring evenly at room temperature of 30°C, then adding to a closed reactor, gradually heating to 210°C at a heating rate of 2°C / min, controlling the pressure of the reactor to be 2.1MPa, and then continuously stirring to react for 10 hours. After the reaction is completed, cool to room temperature, wash, filter and dry to obtain a particle product; S2: adding 1.8 parts of the particle product and 0.42 parts of the composite particles to a mixed solution of 100 parts of water and ethanol (water: ethanol = 4:1), adding 0.12 parts of ammonia water and 0.5 parts of tetraethyl orthosilicate, heating to 60°C, reacting for 2.5 hours, and filtering, washing and drying the product after completion.
[0076] Comparative Example 6
[0077] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified additive comprises the following steps: S1: adding 2.8 parts of chromium nitrate, 0.96 parts of phthalic acid and 11.5 parts of acetic acid to 250 parts of deionized water, stirring evenly at room temperature of 30°C, then adding to a closed reactor, gradually heating to 210°C at a heating rate of 2°C / min, controlling the pressure of the reactor to be 2.1MPa, and then continuously stirring to react for 10 hours. After the reaction is completed, the mixture is cooled to room temperature and washed, filtered and dried to obtain a particle product; S2: adding 3.8 parts of the particle product and 0.15 parts of the composite particle to a mixed solution of 100 parts of water and ethanol (water: ethanol = 4:1), adding 0.18 parts of ammonia water and 1.45 parts of tetraethyl orthosilicate, heating to 60°C, reacting for 3 hours, and filtering, washing and drying the product after completion.
[0078] Comparative Example 7
[0079] The specific implementation of this comparative example is basically the same as that of Example 1, except that the composite particles are zinc oxide, and the average particle size of the zinc oxide is 50 nm.
[0080] The average particle size of the modified additive is 847 nm.
[0081] Performance Evaluation
[0082] Static water adsorption determination: Referring to the standard GB / T 6287-86, the samples obtained in the examples and comparative examples after calcination at 550°C were placed in a saturated sodium chloride solution in a sealed container, and the temperature was set at 25°C and the relative humidity was 75% to reach adsorption equilibrium. The static water adsorption of the molecular sieve activation powder was measured at this time. The test value was the average value of 10 tests and recorded in Table 1.
[0083] Dispersibility test: castor oil was used as a medium, and samples prepared by the embodiment and the comparative example were added at room temperature of 25-30°C, with a mass ratio of castor oil: sample = 3:1. The mixture was stirred at 1000rpm for 15 minutes and then allowed to stand for observation. The stirring step was repeated every other week. The temperature was kept at 25-30°C and the relative humidity was 50-60%. After 8 weeks, it was observed whether there was obvious particle sedimentation, scattered particles, or whether the stirring rod was stuck with sample molecular sieve particles. If any of these items appeared, it was recorded as unqualified. On the contrary, if none of these items appeared, it was qualified. 50 samples were tested in each group to obtain the sample qualified rate, and the results were recorded in Table 1.
[0084] Operability time test: The operability of the polyurethane adhesive of the molecular sieve active powder obtained in the embodiment and the comparative example was tested with reference to GB-T 7123.1-2015 standard. The sample addition amount was 3.25wt% of the total polyurethane adhesive. The polyurethane adhesive was PU-204 polyurethane adhesive product sold by Guangzhou Jibisheng Technology Industrial Co., Ltd. The test value was the average value of 10 tests and recorded in Table 1.
[0085]
[0086] From the data results of the present application examples and comparative examples and Table 1, it can be known that the present application examples 1 and 2 have obvious performance advantages over comparative examples 1 to 7 in the adsorption, dispersibility and operable time of the molecular sieve activation powder. This is because, by adopting the technical solution defined in the present application, embodiments 1 and 2 not only effectively increase the porosity and hole depth of the matrix sieve powder through the raw material ratio of the matrix sieve powder and the selection of the process sequence, but also reduce the lattice defects after crystallization, reduce the activity of the surface groups, and greatly improve the purity of the crystallization through the control of the crystallization process, thereby avoiding the influence of the alkaline substances in the solvent on the final matrix sieve powder performance, greatly reducing the alkalinity of the matrix sieve powder during the application process, thereby avoiding the influence of the self-alkalinity bias of the molecular sieve activation powder on the overall curing time and open time of the adhesive; further, adding modified additives improves the adsorption performance of the molecular sieve active powder, and can also greatly enhance the stability of its molecular sieve composite particles, improve its system dispersion effect, reduce surface viscosity, and thus improve the performance of the adhesive in all aspects. The modified particle skeleton structure can be coordinated and bonded to the surface active groups of the matrix sieve powder, and the sol silica formed is protectively bonded and fixed. The composite structure formed not only increases the total specific surface area and porosity of the unit number of particles, but the micropores of the skeleton particles can also assist in the absorption of water molecules and always keep the fixed water at a limited temperature. However, because the correct limited technical solution was not adopted in Comparative Examples 1 to 7, the corresponding performances have obvious differences, which further proves the necessity of the limited technical solution of this application for the technical effect.
Claims
1. A molecular sieve activation powder for prolonging the curing time of an adhesive, characterized in that: Molecular sieve activation powder for extending the curing time of adhesive, the raw materials include: 60-90 parts of base sieve powder, 10-25 parts of modified additives, 5-20 parts of organic acid anhydride, and 5-10 parts of polysiloxane; The preparation method of the matrix sieve powder comprises the following steps: S1: mixing an aluminum source and a sodium source, adding them into deionized water, and stirring them evenly; S2: heating the solution to 40-60°C, adding a silicon source into the S1 solution, stirring for 20-30 minutes to mix evenly, and adjusting the water content during the process until a gel product is formed after the stirring is completed; S3: placing the gel product into a crystallization kettle, heating the solution to 90-100°C at a speed of 2-4°C / min, and stirring the solution at a speed of 100-200 rpm for 3-5 hours to crystallize the gel product; S4: after the crystallization is completed, the solution is naturally cooled to room temperature to stabilize. The mixture is stored for 30 to 50 hours for aging, and after aging, it is filtered to obtain filter cake I; S5: filter cake I is added to an ion exchange kettle, and an appropriate amount of deionized water is added to disperse and stir for 20 to 30 minutes until it is uniform, and after sufficient water washing, it is filtered twice to obtain filter cake ⅠⅠ; S6: filter cake ⅠⅠ is added to an ion exchange kettle, and an appropriate amount of deionized water and ion exchange agent are added, mixed, dispersed and stirred for 20 to 30 minutes until it is uniform, and then filtered three times to obtain filter cake ⅠⅠⅠ; S7: filter cake ⅠⅠⅠ is ground into powder and calcined at 500 to 600°C for complete activation, and then the material is discharged; The aluminum source is at least one of aluminum oxide, aluminum hydroxide, sodium metaaluminate, and aluminum chloride; The sodium source is at least one of sodium silicate, sodium hydroxide and sodium chloride; The silicon source is sodium silicate or potassium silicate; The mass ratio of the aluminum source, the sodium source and the silicon source is (1-1.2): (0.8-1.2): (2-2.5); The mass ratio of deionized water and filter cake I in S5 is (1-1.2): (0.4-0.6); The mass ratio of deionized water, filter cake ⅠⅠ and ion exchanger in S6 is (1-1.2): (0.4-0.6): (0.1-0.2); The preparation method of the modified additive comprises the following steps: S1: adding aluminum nitrate, terephthalic acid and acetic acid to deionized water and stirring evenly at room temperature, then adding to a closed reactor, gradually heating to 200-210°C at a heating rate of 2°C / min, controlling the pressure of the reactor to be 1.8-2.2MPa, then continuously stirring to react for 8-12h, cooling to room temperature after the reaction is completed, washing, filtering and drying to obtain a particle product; S2: adding the particle product and the composite particle to a mixed solution of water and ethanol, adding ammonia water and tetraethyl orthosilicate, heating to 60-65°C, reacting for 2-4h, filtering, washing and drying the product after completion to obtain; The composite particles are zinc oxide or titanium dioxide; The mass ratio of the aluminum nitrate, terephthalic acid and acetic acid is (2.5-3.5): (0.8-1.4): (10-14); The mass ratio of the particle product, the composite particles and tetraethyl orthosilicate is (1.5-2): (0.3-0.5): (0.4-0.5); The average particle size of the modified additive is 500-650 nm; The ion exchanger is at least one of potassium chloride, calcium chloride, ammonium chloride, magnesium chloride and zinc chloride.
2. The molecular sieve activation powder for prolonging the curing time of the adhesive according to claim 1, characterized in that: The mass ratio of the base sieved powder to the modified additive is (7-8.5): (1.2-2).
3. The molecular sieve activation powder for prolonging the curing time of the adhesive according to claim 2, characterized in that: The aluminum source is sodium aluminate; the sodium source is sodium hydroxide; the silicon source is sodium silicate; and the ion exchanger is potassium chloride.
4. The molecular sieve activation powder for prolonging the curing time of the adhesive according to claim 3, characterized in that: The mass ratio of deionized water, filter cake Ⅱ and ion exchanger in S6 is 1:0.5:0.
1.
5. A method for preparing a molecular sieve activation powder for prolonging the curing time of an adhesive according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1: adding matrix sieve powder to a mixed solution of water and ethanol and dispersing the powder uniformly; S2: adding a mixed ethanol solution of a modified additive and polysiloxane, then dripping an aqueous solution containing an organic acid anhydride into the reaction solution, heating the solution to 55-65°C and stirring the solution for 2-3 hours, and after completion, ultrasonically dispersing the product at 40-50°C and 200-250W for 0.5-1 hour, and after completion, filtering and drying the product to obtain the product.
Citation Information
Patent Citations
Method for preparing nano molecular sieve
CN101182004A
Method for synthesizing ZSM-5 molecular sieve
CN101468807A
Cited By
Flame retardant based on molecular sieve, preparation method of flame retardant and application of flame retardant in polyurethane adhesive
CN121362375A